Encyclopedia of marine science [electronic resource] - Nichols, C. Reid; Williams, Robert G. (Facts on File science library, 2009)
Covers concepts, technologies, phenomena, organisms, legal issues, research stations, vessels, experiments, marine sanctuaries, scientists, lawmakers, programs, organizations, careers, and other subjects related to marine science